Using pano-mapping tables for unwarping of omni-images into panoramic and perspective-view images - Jeng, S. W.; Tsai, W. H. (My University, 2007)
A unified approach to unwarping of omni-images into panoramic or perspective-view images is proposed. The approach does not adopt the conventional technique of calibrating the related parameters of an omni-camera. Instead, it is based on a new concept of a pano-mapping table, which is created once forever, by a simple learning process for an omni-camera of any kind, as a summary of the information conveyed by all the camera parameters. The learning process takes, as input, a set of landmark point pairs, in the world space and in a given image. With the help of the pano-mapping table, any panoramic or perspective-view image can be created from an input omni-image taken by the omni-camera, according to an analytic computation process proposed in the paper. Experimental results show the feasibility of the proposed approach.